HUBUNGAN TINGKAT ANXIETY DENGAN KONTROL ASMA BRONKIAL - Marlin Sutrisna; Elsi Rahmadani (Poltekkes Kemenkes Medan, 2022)
Bronchial asthma is still a health problem that is included in the top 10 deadly diseases in the world. The purpose of this study was to determine the relationship between Anxiety Levels and Control of Bronchial Asthma. The type of research used is descriptive research with a cross sectional research design. The place of research was carried out at the Sukamerindu Health Center in 2020. The sample in this study was bronchial asthma patients, totaling 30 respondents. Measurement of anxiety level using the HARS scale instrument and measurement of bronchial asthma control using the ACT (Asthma Control Test) instrument. Data were analyzed by chi-square. The results showed that more than some respondents had controlled asthma and more than some respondents did not experience anxiety (normal). The results of the chi-square statistical test showed that there was a relationship between anxiety levels and control of bronchial asthma in the Sukamerindu Pueskesmas Work Area, Bengkulu City. The conclusion in this study is that the level of anxiety can affect the control of bronchial asthma. Researchers suggest that the Sukamerindu Public Health Center can provide education to asthma patients so that they can control their anxiety so that asthma becomes more controlled.